The association of educational attainment, cognitive level of job, and leisure activities during the course of adulthood with cognitive performance in old age: the role of openness to experience. (26th November 2015) - Ihle, Andreas; Oris, Michel; Fagot, Delphine; Maggiori, Christian; Kliegel, Matthias
ABSTRACT: Background: The relevance of mental health for everyday life functioning and well-being is crucial. In this context, higher educational attainment, higher cognitive level of one's occupation, and more engaging in stimulating leisure activities have been found to be associated with better cognitive functioning in old age. Yet, the detailed pattern of the potential interplay of such a cognitively engaged lifestyle with personality dimensions, such as openness to experience, in their relations to cognitive functioning remains unclear. Methods: Two thousand eight hundred and twelve older adults served as sample for the present study. Psychometric tests on verbal abilities and processing speed were administered. In addition, individuals were retrospectively interviewed on their educational attainment, occupation, and regarding 18 leisure activities that had been carried out in mid-life. Moreover, openness to experience was assessed. Results: We found that the effect of openness to experience on cognitive functioning was mediated by educational attainment, cognitive level of job, and engaging in different leisure activities. Data were not better described by alternative moderation models testing for interactive (i.e. dependent) effects of openness to experience and cognitively stimulating engagement. Conclusions: To explain interindividual differences in cognitive functioning in old age, present data are in line with a mechanism in which individuals with high openness to experience may have been more engaged in stimulating activities in early and mid-life. Possibly by increasing their cognitive reserve throughout adulthood, this may finally enhance their cognitive performance level later in old age.